The Resistance of Spodoptera frugiperda to Carbamate-Class Insecticides in Serang Regency, Indonesia - Cahyani Nufus; Julio Eiffelt Rossaffelt Rumbiak; Andi Apriany Fatmawaty; Andree Saylendra (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2026)
Spodoptera frugiperda is a pest native to tropical and subtropical America. This pest is invasive and has spread to other parts of the world. Farmers use synthetic chemical pesticides in pest control because they are easily available and have a rapid population suppression rate. Carbamates are a group of insecticide compounds that have the potential to disrupt the central nervous system. Resistance is a negative impact of irresponsible insecticide use. This study aims to determine the level of resistance of Spodoptera frugiperda to synthetic carbamate insecticides. The study used a completely randomized design (CRD) consisting of two factors. The first factor was the insecticide treatment, including control (no insecticide), carbaryl, methomyl, and carbofuran. The second factor was the concentration levels of 5%, 20%, 50%, 75%, and 95%, with three replications for each treatment. Data were analyzed using analysis of variance (ANOVA), probit analysis (SPSS software), and Duncan's Multiple Range Test (DMRT) as a post hoc test. The results indicated that field populations of Spodoptera frugiperda in Serang Regency, Indonesia, were suspected of having developed resistance to carbaryl. Differences in insecticide performance among the tested carbamate active ingredients highlight the importance of selecting effective insecticides for S. frugiperda management. Based on the LT and LC values, methomyl exhibited the highest toxicity among the tested carbamate insecticides and may be considered a potential option for managing S. frugiperda, although further field validation is recommended. This study also documented changes in larval body morphology, coloration, and odor following exposure to the tested insecticides.